2004
DOI: 10.1021/la0491293
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Match between Cholesterol and Saturated Fatty Acid Is Required for the Formation of Lamellar Liquid Ordered Phases

Abstract: Palmitic acid and cholesterol have been shown to form, under certain conditions, bilayers in the liquid ordered (lo) phase. In the present work, the contribution of the hydrophobic match between cholesterol (chol), and the acyl chain of saturated fatty acids (FA) has been examined. The behavior of FA/chol mixtures where the FA acyl chain length was varied between 12 and 24 carbon atoms was investigated by infrared and 2H NMR spectroscopy, as well as by differential scanning calorimetry. It was found that only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 61 publications
6
69
0
Order By: Relevance
“…Ouimet et al were experimentally able to observe bilayer formation with C14:0 and C18:0 acids mixed with cholesterol, but not for mixtures containing fatty acids with tails longer than 18 carbons or shorter than 14 carbons. 34 The authors hypothesized that fatty acids with short or long tails cannot form a bilayer with cholesterol because of the hydrophobic size mismatch between the two molecules, 34 while hexadecanoic acid’s and cholesterol’s matching length permits strong van der Waals interactions.…”
Section: Coarse-grained Bilayer Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ouimet et al were experimentally able to observe bilayer formation with C14:0 and C18:0 acids mixed with cholesterol, but not for mixtures containing fatty acids with tails longer than 18 carbons or shorter than 14 carbons. 34 The authors hypothesized that fatty acids with short or long tails cannot form a bilayer with cholesterol because of the hydrophobic size mismatch between the two molecules, 34 while hexadecanoic acid’s and cholesterol’s matching length permits strong van der Waals interactions.…”
Section: Coarse-grained Bilayer Resultsmentioning
confidence: 99%
“…33, 34 In the experimental work, the phase behavior of cholesterol and C16:0 in well-hydrated mixtures was examined and the effects of temperature and lipid composition determined. The authors found cholesterol and C16:0 existed in a bilayer phase only at temperatures between the melting points of the acid and cholesterol (between 328 K and 422 K); outside of this range, the experimental data suggested high concentrations of cholesterol exist locally within the bilayer in cholesterol-rich domains.…”
Section: Introductionmentioning
confidence: 99%
“…For clarity, a sketch of the proposed assembly of two IPM molecules has been added to figure 3. Due to the hydrophobic match [23], the C14 chain of IPM will have high affinity to the C16 fatty acid (PA) present in the mixture and stretches through one hydrophobic bilayer leaflet. The more hydrophilic ester group most likely lies in the bilayer head group region, where hydrogen bonds with the other SC lipid head groups stabilize this arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…31,52 It has been discussed that the chain-length match is the determining factor that dictates the mixing and phase behavior of ternary mixtures of Cer, free fatty acids, and Chol. 26,27 For the formation of the liquid-ordered phase, the hydrophobic match between Chol and the saturated fatty acid is required, 53 26 revealed the complex phase behavior of this allegedly simple ternary lipid mixture. The authors conclude that the acyl chain heterogeneity of Cer appeared to be more important for lipid miscibility than hydrophobic chain matching.…”
Section: ■ Introductionmentioning
confidence: 99%